Surface N- or O-linked glycans on bovine spermatozoa play minimal role in evading macrophage mediated phagocytosis - Chera, Jatinder Singh; Gaur, Vikrant; Kumar, Abhishek; Josan, Fanny; Patel, Aditya; Yadav, Sonam; Karanwal, Seema; Verma, Preeti; Verma, Vivek; Kumar, Sushil; Bairagi, Amit Kumar; Kamal, Sanchi; et al. (Frontiers in Veterinary Science, 2025)
Bull spermatozoa possess glycocalyx made of carbohydrate moieties attached to proteins and lipids on their membranes that is involved in fertility associated functions including immune evasion in the female reproductive tract. The current study aimed to establish whether the differences in the glycocalyx of spermatozoa provide selective advantage in evading phagocytosis mediated by female macrophages. Based on removal of either N- or O-linked surface glycans from the spermatozoa, their susceptibility to phagocytosis by macrophages was assessed in vitro in bovines (Bos indicus) through flow cytometry. We found no significant difference (p > 0.05) in the phagocytosis of spermatozoa without N-glycans or O-glycans compared to those with intact glycocalyx. Out of nearly 2,000 events analysed, the mean number of macrophages phagocytosing the spermatozoa were found to be 416, 423 and 345, respectively for spermatozoa with an intact glycocalyx, with N-glycans removed and with O-glycans removed. The difference in the mean values of the individual sample geometric mean fluorescence intensities (n = 3) of the phagocytosed spermatozoa among all the treatment groups were also statistically insignificant (p > 0.05) indicating that the macrophages are not involved in the selection of spermatozoa based on their surface glycan profiles. Therefore, it is plausible to conclude that macrophages may be exploiting other signature molecules if at all they are involved in the cryptic female choice, or they might be phagocytosing spermatozoa with less stringency that may not be dependent on O- or-N-glycans on sperm surface. However, further studies are required to gain deeper insights into this phenomenon.